Depressive Symptoms and Memory Performance Among Older Adults: Results From the ACTIVE Memory Training Intervention. (December 2013) - Lohman, Matthew C.; Rebok, George W.; Spira, Adam P.; Parisi, Jeanine M.; Gross, Alden L.; Kueider, Alexandra M.
Background: Cognitive performance benefits from the Advanced Cognitive Training for Independent and Vital Elderly (ACTIVE) study may differ for individuals who exhibit a greater number of depressive symptoms. Method: Using data from ACTIVE memory training and control conditions, we evaluated the effect of depressive symptomatology on memory scores across a 5-year period. Of 1, 401 participants, 210 had elevated depressive symptoms at baseline, as measured by a 12-item version of the Center for Epidemiological Studies-Depression Scale (CES-D). Results: Participants with elevated depressive symptoms scored significantly lower at baseline and had faster decline in memory performance than those exhibiting fewer depressive symptoms. Memory score differences among depressive symptom categories did not differ between training conditions. Discussion: Findings suggest that elevated depressive symptoms may predict declines in memory ability over time, but do not attenuate gains from training. Training provides a potential method of improving memory which is robust to effects of depression.